O papel das tecnologias da informação na proposição de valor para a economia circular à luz do tripé da sustentabilidade: um estudo em empresas do setor de gestão de resíduos e reciclagem - Martins, Leonardo Medeiros (2021)
The literature about sustainability indicates a gap of empirical studies on the role of information technologies (IT) in the circular economy's value proposition. At the same time, it indentifies a lack of researchs about how the systemic approach supports the circular economy characteristics' understanding, been represented here by the tiple bottom line. Based on this context and viewing the theme's relevance, the aim of the work is to investigate the information technolgies' role in the value proposition of business models at circular economy, under a systemic approach of sustainability. Therefore, it was done a descriptive and qualitative nature research, in two steps. The first was a bibliographical research that had as result a conceptual framework to understand the circular economy over the triple bottom line. The second step consisted in a documental research through the collection of 62 documents, between news and business reports, of 21 startups inserted on waste management and recycling sectors. The thematic analysis was the chosen technic to analyze the bibliographical and documental data. As result, it was evidenced that the functions of sensoring, tracking, conectivity and processing could increase the business model to innovate traditionally analogical sectors, principally through technologies such as internet of things, artificial intelligence, cloud computing and big data. Another important finding is tha the IT favours a value proposition based on efficient use or substitution of resources, which implies in positive environmental effect. Lastly, it is pointed that is necessary build an interaction with the partners and business participants to support and disseminate the circular economy's business value up to the social sphere.